The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1126/sciadv.ade0413
|View full text |Cite
|
Sign up to set email alerts
|

Toward a universal framework for evaluating transport resistances and driving forces in membrane-based desalination processes

Abstract: Desalination technologies using salt-rejecting membranes are a highly efficient tool to provide fresh water and augment existing water supplies. In recent years, numerous studies have worked to advance a variety of membrane processes with different membrane types and driving forces, but direct quantitative comparisons of these different technologies have led to confusing and contradictory conclusions in the literature. In this Review, we critically assess different membrane-based desalination technologies and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 116 publications
0
13
0
Order By: Relevance
“…The lack of a measurable change in salt rejection as the thickness decreased was consistent with our understanding that selectivity in the air-trapping membranes is attributable to the gas-liquid phase change transport mechanism. Because of their low thicknesses, the water permeabilities of membranes in this work were notably higher than previous work in osmotic and membrane distillation systems, where membranes are tens of micrometers thick and generally have water permeabilities one to two orders of magnitude lower ( 21 ). While the aim of this study was not to produce membranes that outcompete commercial RO membranes in terms of water permeability, our measurements provide experimental evidence that it is possible for air-trapping membranes to reach the water permeabilities needed for efficient water desalination ( 27 ).…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…The lack of a measurable change in salt rejection as the thickness decreased was consistent with our understanding that selectivity in the air-trapping membranes is attributable to the gas-liquid phase change transport mechanism. Because of their low thicknesses, the water permeabilities of membranes in this work were notably higher than previous work in osmotic and membrane distillation systems, where membranes are tens of micrometers thick and generally have water permeabilities one to two orders of magnitude lower ( 21 ). While the aim of this study was not to produce membranes that outcompete commercial RO membranes in terms of water permeability, our measurements provide experimental evidence that it is possible for air-trapping membranes to reach the water permeabilities needed for efficient water desalination ( 27 ).…”
Section: Resultsmentioning
confidence: 61%
“…This pressure-driven distillation process can retain the high energy efficiency and small footprint of RO but also achieve complete removal of nonvolatile species and tolerate harsh feedwaters ( 20 ). Pressure-driven distillation distinguishes itself from existing thermal membrane distillation since it does not require heat energy and is distinct from osmotic distillation, which requires a secondary separation step ( 21 ). The feasibility of desalination via pressure-driven distillation is evident from theory, but demonstration of the system has not been possible due to a lack of appropriate membranes for the process ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…1 Desalination of brackish water and seawater provides a feasible pathway to alleviate the freshwater scarcity. 2 However, vast quantities of concentrated wastewater are produced as a byproduct. 3 Additionally, a large volume of freshwater has been consumed and converted to hypersaline wastewater associated with intensive industrial activities.…”
Section: ■ Introductionmentioning
confidence: 99%
“…14 Modeling work has shown that the energy efficiency of PD is likely similar to that of RO since both are driven by hydraulic pressure, and detrimental heat transfer effects in PD are minimal for all realistic membrane properties. 15,16 Despite the potential benefits of PD in desalination and other separations, few studies have experimentally investigated the process, in part due to the challenge of operating airtrapping membranes at pressures above 5 bar without wetting. Those studies that have been conducted have gleaned important insights on the process, showing that PD is experimentally viable, that PD membranes can reach water permeabilities comparable to RO membranes, and that PD can highly reject boron, urea, and other contaminants.…”
Section: ■ Introductionmentioning
confidence: 99%
“…PD is also similar to membrane distillation (MD) in that transport occurs in the vapor phase through porous hydrophobic membranes; the main difference between PD and MD is that pressure is the driving force in PD rather than temperature, making PD a more energy efficient method of separation . Modeling work has shown that the energy efficiency of PD is likely similar to that of RO since both are driven by hydraulic pressure, and detrimental heat transfer effects in PD are minimal for all realistic membrane properties. , …”
Section: Introductionmentioning
confidence: 99%